2018
DOI: 10.3390/nu10030277
|View full text |Cite
|
Sign up to set email alerts
|

Lower Vitamin D Status Is Associated with an Increased Risk of Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: In recent years, accumulating evidence has supported the hypothesis that lower vitamin D status is associated with several known risk factors of stroke. However, the relationship between vitamin D and stroke is still uncertain. To explore if there was an association between vitamin D status and the risk of stroke, a systematic review and a meta-analysis were conducted by searching three databases: Pubmed, Embase, and the Cochrane Library. Following the application of inclusion and exclusion criteria, the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 40 publications
(35 reference statements)
2
67
0
1
Order By: Relevance
“…A logistic regression analysis revealed independence of vitamin D in the disease status where vitamin D insufficiency increases the risk of stroke severity by 2.884 times whereas vitamin D deficiency increases the severity 13.78 times. These findings came in agreement with Makariou and colleagues [6], also Zhou and colleagues [5]. Another logistic regression analysis was done to evaluate the independence of vitamin D in the disease outcome.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A logistic regression analysis revealed independence of vitamin D in the disease status where vitamin D insufficiency increases the risk of stroke severity by 2.884 times whereas vitamin D deficiency increases the severity 13.78 times. These findings came in agreement with Makariou and colleagues [6], also Zhou and colleagues [5]. Another logistic regression analysis was done to evaluate the independence of vitamin D in the disease outcome.…”
Section: Discussionsupporting
confidence: 87%
“…Large epidemiological studies indicated an association between vitamin D status and risk of stroke [5]. However, the relationship between different vitamin D states in acute ischemic stroke patients as well as exploring vitamin D as an independent risk factor for acute ischemic stroke need more elucidation [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As a neurosteroid, vitamin D plays a vital role in preventing vascular injury through the mechanism of inhibiting the renin-angiotensin-aldosterone system and atherogenesis [7], lowering blood pressure, reduction in endothelial dysfunction [13], and neuroprotective actions in stroke [14]. Accumulating data have supported the hypothesis lower 25(OH)D level was associated with ischemic stroke, higher mortality and poor outcome [15][16][17][18][19][20][21][22][23][24][25][26], and a higher vitamin D was linked to a decreased risk of cerebrovascular disease [27]. These findings were also substantiated by the evidence of meta-analysis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Third, we did not classify SVD into different types according to STRIVE such as lacunes, WMHs, CMBs or PVS [8,52], and we did not assess the total SVD burden (0 to 4) [10]. Further studies are required to confirm this association and explore the association among different subtypes of SVD [8,17]. Fourth, there were some different categories according to levels of vitamin D (stratified into 2 or 3 or 5) in different studies [38,53], such as deficiency (< 25 nmol/L or < 20 ng/mL), insufficiency (25-50 nmol/L or 20-30 ng/mL), sufficiency (≥50 nmol/L or ≥ 30 ng/mL) [44,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D and risk of stroke [16,[57][58][59][60][61][62][63][64][65][66] Vitamin D and outcome of stroke [3,[11][12][13][14][15][67][68][69][70][71] Supplementation of Vitamin D and post-stroke recovery [67,72,73] Vitamin D and rehabilitation after stroke [3,[12][13][14][15]74] Appl. Sci.…”
Section: Topic Referencesmentioning
confidence: 99%